HUBUNGAN PENGETAHUAN IBU POST PARTUM DENGAN TEKNIK MENYUSUI YANG BENAR DI KLINIK MARIANA MEDAN TAHUN 2016 - Debi Novita Siregar; Martauli Pane (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2017)
ABSTRACT The correct breastfeeding technique is one of the factors that affect breast milk production, if improper breast-feeding techniques can cause nipple blisters and make the mother reluctant to suckle. Based on Indonesia Demographic and Health Survey (2008-2009), 55% of breastfeeding mothers suffer from mastitis and scuffed nipples, this is due to improper breastfeeding techniques.The purpose of this research is to know the relationship of post partum pregnant woman with correct breastfeeding technique at Mariana Clinic Medan Year 2016. This research use descriptive research type with cross sectional design. The population in this study were 28 post partum mothers. Sampling in this study using accidental sampling technique, the number of samples of 9 post partum mothers. This research use primary data and secondary data then chi square test.Based on the research result, post partum mother with good knowledge of 5 postpartum mothers, mothers with enough knowledge of 3 postpartum mothers, and mothers with less knowledge as much as 1 post partum mother. The majority of postpartum mothers with correct breastfeeding techniques were 6 postpartum mothers, and mothers with the wrong breastfeeding technique were 3 post partum mothers. The results show X ² 6000> X ²table 5.991.The conclusion of this research is there is correlation between knowledge of mother of post partum with correct breastfeeding technique at Mariana Clinic Medan Tahun2016.Saran in this research is for the respondent to increase knowledge about correct breastfeeding technique, to educational institution to improve the quality of education, to the next researcher for more accurate search results. Keywords: Knowledge, Mother Post Partum, Right Breastfeeding Technique